2019
DOI: 10.15694/mep.2019.000046.1
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety and Quality of Care are Everybody's Business: Evaluating the Impact of a Continuing Professional Development Program beyond Satisfaction

Abstract: BackgroundResearch integrating Continuing Professional Development (CPD) with patient safety (PS) and quality improvement (QI) is still in its infancy despite advocacy by leaders in the field. ObjectivesThis theory-driven study explored the feasibility to implement and evaluate the impact of a CPD intervention focused on teaching and practicing PS and QI at the levels of satisfaction, usefulness, knowledge, confidence, intention to change behaviour and reported changes in practice. MethodsThree workshops targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Of all the studies, 69% (36/52) were published between 2019 and 2021 [ 9 , 32 - 68 ]. Furthermore, 58% (30/52) were located in Canada [ 7 , 8 , 10 - 12 , 23 - 25 , 28 , 31 , 35 , 38 - 41 , 44 - 51 , 53 , 54 , 56 , 60 , 63 , 65 , 67 ] and the rest in the United States (n=6), the United Kingdom (n=4), Australia (n=2) [ 30 , 34 ], Iran (n=2) [ 55 , 64 ], Argentina (n=1) [ 52 ], Indonesia (n=1) [ 32 ], Germany (n=1) [ 58 ], Sweden (n=1) [ 21 ], the Netherlands (n=1) [ 59 ], and Burkina Faso (n=1) [ 37 ]. In addition, two multicountry studies were reported: 1 from Brazil-China-France-Japan-Mali [ 68 ] and 1 from Canada-Vietnam [ 19 ] ( Table 1 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all the studies, 69% (36/52) were published between 2019 and 2021 [ 9 , 32 - 68 ]. Furthermore, 58% (30/52) were located in Canada [ 7 , 8 , 10 - 12 , 23 - 25 , 28 , 31 , 35 , 38 - 41 , 44 - 51 , 53 , 54 , 56 , 60 , 63 , 65 , 67 ] and the rest in the United States (n=6), the United Kingdom (n=4), Australia (n=2) [ 30 , 34 ], Iran (n=2) [ 55 , 64 ], Argentina (n=1) [ 52 ], Indonesia (n=1) [ 32 ], Germany (n=1) [ 58 ], Sweden (n=1) [ 21 ], the Netherlands (n=1) [ 59 ], and Burkina Faso (n=1) [ 37 ]. In addition, two multicountry studies were reported: 1 from Brazil-China-France-Japan-Mali [ 68 ] and 1 from Canada-Vietnam [ 19 ] ( Table 1 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…( Table 2 ). In most studies, participants in CPD activities consisted of interprofessional groups (30/52, 60%) [ 7 , 9 - 11 , 19 , 21 , 27 , 28 , 31 , 35 , 37 , 41 , 43 , 44 , 46 , 47 , 50 , 51 , 53 , 55 - 61 , 63 , 64 , 66 - 68 ]. Professions included nurses (5/52, 10%) [ 26 , 29 , 30 , 48 , 54 ], physicians (4/52, 8%) [ 38 , 39 , 49 , 52 ], social workers or other health professionals, namely occupational therapists, physiotherapists, dietitians, behavioral counselors, nutritionists, health researchers (4/52, 8%) [ 23 - 25 , 34 , 36 ], specialist physicians (3/52, 6%) [ 32 , 40 , 65 ], and pharmacists (2/52, 4%) [ 22 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a thematic analysis of qualitative data, descriptive statistics and triangulation of sources they could show "feasibility to develop and implement an effective CPD intervention supporting healthcare professionals' knowledge, confidence, and reported change in teaching and practicing PS-QI". (Luconi F, Boillat M, Mak S, Chartrand D, et al, 2019) Haruta and associates aimed to assess the validity and reliability of the Interprofessional Performance Scale in Conference (IPLSC). Their work allowed them to state that the IPLSC is a valuable evaluation tool to make consistent assessments of interprofessional performance in conferences.…”
Section: Research Articlesmentioning
confidence: 99%
“…Lifelong learning among healthcare practitioners is important to keep pace with rapid transformations which inform the practice environment [ 1 ], ensure patient safety and quality of care [ 2 ]. Two approaches that have been used to ensure and promote lifelong learning globally in pharmacy include continuing professional development (CPD) and continuing (pharmacy/medical) education (CE) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%